Digital Modulation using Spread Spectrum Technique(DMSST) - VAKRAM CHATTA, VILJA ALISWA C K, VISHAL KOUL and ROSEMARY SHERIN K (2000)
INTERNAL GUIDE: SUMA, MVJCE EXTERNAL GUIDE: ANAND KRISHNA V T, SENIOR MANAGER HAL, BANGALORE
Keywords: Spread Spectrum Technique